The potential of low‐intensity pulsed ultrasound to apply the long‐term ovary protection from injury induced by 4‐vinylcyclohexene diepoxide through inhibiting granulosa cell apoptosis - Juan Deng; Juan Qin; Guolin Song; Chenghai Li; Wentao Tang; Yilin Tang; Xinfang Xiao; Liu Wu; Sicheng He; Yiqing Zhou; Junfen Li; Yan Wang (Bioengineering & Translational Medicine)
Abstract The potential of low‐intensity pulsed ultrasound (LIPUS) in regulating ovarian function has been demonstrated; however, there is a lack of scientific evidence regarding the long‐term efficacy of LIPUS in treating ovarian injury and understanding its regulatory mechanisms. In this study, 4‐vinylcyclohexene diepoxide (VCD) was used to induce ovarian injury in rats, and LIPUS was applied to target the damaged ovarian tissues. The research aimed to investigate the long‐term protective effect of LIPUS against ovum toxicity induced by VCD and elucidate the associated molecular mechanisms. During the experiment, HE staining was employed for observing the morphology and structure of the ovary, while protein sequencing was utilized for identifying and confirming the molecular mechanism through which LIPUS restores the damaged ovarian structure. The long‐term effectiveness of LIPUS in protecting against ovarian injury was evaluated through ELISA, estrous cycle monitoring, fertility testing, and behavioral analysis. The results indicated that LIPUS effectively restored the structure of damaged ovaries. Both in vivo and in vitro studies revealed that this protective effect may be attributed to LIPUS inhibiting apoptosis of ovarian granulosa cells (GCs) by regulating Daxx‐mediated ASK1/JNK signaling pathway. Subsequent functional tests demonstrated significant improvements in sex hormone secretion and regulation of estrous cycle within 6 cycles following LIPUS treatment. Additionally, there was a notable increase in offspring numbers after mating. Behavioral analysis revealed that LIPUS effectively alleviated menopausal symptoms resulting from ovarian injury including mood fluctuations, cognitive behavior changes, and reduced muscle excitability levels. These findings suggest that beneficial effects of LIPUS may help reduce VCD‐induced ovarian damage with long‐term efficacy.